LATE PALEOZOIC ICE AGE: OCEANIC GATEWAY OR PCO2? - Saltzman M.A. (My University, 2003)
The cause of the late Paleozoic (ca. 355 255 Ma) ice age remains uncertain. A lowering of atmospheric carbon dioxide levels near the beginning of this time period occurred in response to the rise of land plants and likely cooled Earth, but the rapid growth of extensive Gondwanan ice sheets was delayed for tens of millions of years, until the Late Mississippian. The delta13C values from a thick succession at Arrow Canyon, Nevada, indicate a divergence between North America and Europe (˜20/00) across the Mississippian-Pennsylvanian transition, and support a scenario in which the closure of a subequatorial oceanic gateway during the assembly of Pangea altered the oceanic distribution of nutrients (12C) and led to enhanced poleward transport of heat and moisture. This change marks the transition from a cool, moisture-starved Gondwana to the icehouse world of the Pennsylvanian and Early Permian.
Keywords: Carboniferous; glaciation; carbon isotope; Arrow Canyon; oceanic gateway; Paleozoic::Carboniferous; Палеозой::Каменноугольная